Resistance and Adaptation in Banyumas Traditional Gending: Musical Negotiation between Cultural Preservation and Commercial Performance in Lengger and Ebeg - Darno, Darno; Mahatmajangga, Binarung (Bahasa dan Seni: Jurnal Bahasa, Sastra, Seni, dan Pengajarannya, 2026)
This study investigates the musical dynamics of Banyumas-style traditional gending within the contestation of Lengger and Ebeg performances amid the demands of modern entertainment. Using a qualitative method combining ethnomusicological and cultural-sociology perspectives, the study examines changes in musical structure and the socio-cultural forces driving them, and asks specifically: what defines Banyumas gending musicality at the level of instrumental garap (working practice); what concrete forms of adaptation and resistance are observable in contemporary performance; and how these dynamics can be read through Merriam's concept of stability and change and Bourdieu's theory of capital and field. Data were collected through in-depth interviews with masters and cultural practitioners and direct observation of performances across three Banyumas sub-regions. The results show a continuous negotiation between the preservation of local musical convention (pakem) and the pragmatism of market taste. Adaptation manifests as the simplification of instrumental structure and the integration of popular songs to serve a commercial entertainment function, while cultural resistance is sustained through commmunity-based studios, formal-school instruction, and the intergenerational transmission of classical techniques. The study concludes that the survival of Banyumas musicality depends on a dialectical balance between structural resistance and pragmatic adaptation, and it proposes that this balance be read as an evolving field position rather than a fixed opposition.